Case Report: A rare case of gastric-type adenocarcinoma of stumps of duplicated cervices in a 49-year-old woman: A case with hidden focus confused us a lot - You, Xiaolin; He, Li; Lin, Yonghong; Huang, Lu; Wang, Xihao; Wang, Zhigang (Frontiers in Oncology, 2023)
Gastric-type endocervical adenocarcinoma (G-EAC) is a rare special type of cervical mucinous adenocarcinomas, and it is reported the incidence is unrelated to human papillomavirus infection. We report a rare case of G-EAC in stumps of duplicated cervices in a 49-year-old female patient. The woman complained of post-coital bleeding. She had a didelphic uterus with a duplex cervix, and had undergone subtotal hysterectomy 16 years ago. Gynecological examination revealed a normal-appearing right cervix, but the nondominant side of the left cervix, which was buried and covered by the side wall of the left vagina, was difficult to view. After exposing, the left side cervix presented a mature appearance which was smaller than a normal cervix. Her serum carbohydrate antigen-19-9 levels was 112.59 U/ml. The right cervix's cytology was normal, whereas the left cervix had unusual glandular epithelial cells. HPV testing on both cervical smears was negative. Adenocarcinoma was identified at 3, 6, 12 o'clock at the right cervix in a colposcopy-directed punch biopsy, while no abnormality was found in the left cervix or in the curettage of the double cervices. Pelvic magnetic resonance imaging (MRI) revealed two cervical canals, with a 1.9cm×1.6cm mass inside the left cervix, and the left wall of the right cervix may be involved by the tumor of the left cervix. After much deliberation, we considered that the patient had adenocarcinoma of the left cervix stage (IB1, FIGO 2018) and stage T1b1N0M0 (AJCC 2017). Then, the patient underwent radical cervical resection with bilateral salpingo-oophorectomy and bilateral pelvic lymphadenectomy. Her final histopathology indicated G-EAC of the duplicated cervices. After surgery, she received concurrent chemoradiation. Currently, 27 months after the final chemotherapy was administered, the patient remains healthy. Because G-EAC with duplicated cervices is an uncommon cunning tumor with a bad prognosis, early identification and therapy are recommended to enhance the prognosis. The comprehensive evaluation of symptoms and gynecological examination with cervical cytology, colposcopy-directed punch biopsy, endocervical curettage and MRI examine together may assist in determining an accurate preoperative diagnosis.